Biocompatible and antibacterial Flammulina velutipes-based natural hybrid cryogel to treat noncompressible hemorrhages and skin defects - Zhu, Yufan; Chen, Feixiang; Wu, Minhao; Xiang, Jieyu; Yan, Feifei; Xie, Yuanlong; Tong, Zan; Chen, Yun; Cai, Lin (Frontiers in Bioengineering and Biotechnology, 2022)
Hemorrhage, infection and frequent replacement of dressings bring great clinical challenges to wound healing. It is a long-term task to develop dressings with multifunctional biological activities. The application of natural polymers is considered as an effective strategy to improve the bioactivity of various existing biomaterials. In this work, Flammulina velutipes extract (FV) and hydroxyethyl cellulose (HEC) were chemically cross-linked to obtain porous HFV cryogels (named HFVn, with n = 10, 40 or 70 corresponding to the weight percentage of the FV content). We investigated the physical properties, chemical composition and biological activity of HFVs. All groups of HFVs showed good cyto- and hemocompatibility. Among them, HFV70 showed an interconnected macroporous sponge like structure, effectively mimicking the extracellular matrix microenvironment and supporting the adhesion and proliferation of L929 cells. In vivo experiments confirmed that its excellent swelling and shape memory properties enabled rapid and effective hemostasis, with effects comparable to those of commercial gelatin sponges. Additionally, the excellent antibacterial, anti-inflammatory, pro-angiogenic and pro-re epithelialization abilities of HFV70 were also confirmed. Consequently, as-prepared multifunctional cryogel dressing shows promising potential to perform better therapy efficacy in clinic for rapid hemostasis and accelerating wound healing.